Analysis of the Effect of Customer Satisfaction of Internet Service Providers Using Structural Equation Modeling - Veta Lidya Delimah Pasaribu; Fadillah; Ugeng Budi Haryoko (International Journal of Integrative Sciences, 2023)
Service Quality Variable (X1) significantly affects Customer Satisfaction because the probability of t count is smaller than the probability value of 0.05 (0.005 <0.05). Service_Quality Variable (X1) has a direct effect on_Customer_ Satisfaction of 0.365. Product Quality Variable (X2) significantly influences Customer Satisfaction because the probability of t arithmetic is smaller than the probability value of 0.05 (0.005 <0.05). Product Quality Variable (X2) has a direct influence on Customer_Y Satisfaction of 0.432. Quality_X1_Quality Variable, Product_X2_Quality has a 31.7% role to Customer_Y Satisfaction